TINGKAT RASA NYERI PENGAMBILAN DARAH VENA DIBANDING DENGAN DARAH KAPILER TUMIT BAYI KURANG BULAN - , Marti Astuti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Blood sampling in preterm baby is the common procedure that used for laboratory examinations. The experience of pain in early neonatal life is believed to cause chronic pain in adult, leading to increase morbidity, mortality and increasing time of hospitalization in the NICU. There were many studies about procedural pain in full-term baby were used as subject, but none of them used the preterm. The aim of this study is to compare the pain response (PIPP score) of heel blood sampling to venous in preterm infants. The study design was quasi experimental in which the sampling of blood is adjusted based on the indication without randomization. As many as 60 new babies born in some general hospital in Middle Java and Yogyakarta, Indonesia from January 2011 with gestational age of 32 - <37 weeks included in this study after fulfilling inclusion and exclusion criteria. Pain response were observed according to the recording changes in physiological responses, contextual and behavioral response to pain and then assessed with pain instruments Premature Infant Pain Profile (PIPP). Basic characteristic data were homogen between two group (p>0,05). There was no significant differences between PIPP score in venepuncture compare to heelprick (kolmogorov smirnov test, p=0,775). Univariate analysis x2 showed that gender and or prior exposure to pain are not influencing the respons of pain in preterm (p=0,667